KOMPETENSI KEWIRAUSAHAAN PETERNAK SAPI PERAH, KASUS PETERNAK SAPI PERAH DI KABUPATEN BANDUNG JAWA BARAT - Krismiwati Muatip; Basita G. Sugihen; Djoko Susanto; Pang S. Asngari (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2008)
The objectives of the study are as follows: (1) to analyze the entrepre-neurship competence level of dairy farmers, (2) to find out factors that influence the entrepreneurship competence, and (3) to formulize a model of extension service for dairy farmers to improve their entrepreneurship competence level. The research study was conducted at Bandung Regency West Java. The respondents were 151 dairy farmers selected randomly; and the data collected using questionnaires and observation. The number of sample was determined based on Slovin’s formula. Statistical analyses used were correlation, regression and path analysis. The major findings of the study are that the entrepreneurship competence levels of the dairy farmers at the medium category. Factors that influence the entrepreneurship competence of the farmers are their education background and the number of family members, lacking of facilities, informations, and the policy of the government. Extension’s strategies for the entrepreneurship competence improvement are through sthrenghtening of non formal education, and more involvement of family members in daily activities, improvement of daily facilities, informations and sthrenghtening government support.